Microbial Diversity and Antimicrobial Susceptibility from Wound Dehiscence Isolates in an Indonesian Tertiary Referral Hospital (Majalah Kedokteran Bandung, 2024)
Healthcare-associated infections (HAIs) remain a critical issue for public health in Indonesia, with wound dehiscence associated with surgical site infections (SSIs) being one of them. Globally, SSIs are known as the most common postoperative complications with a heightened prevalence, particularly in low to middle-income countries. With its retrospective and descriptive design, this study aimed to illustrate the microbial patterns identified in Prof. Dr. I.G.N.G. Ngoerah General Hospital from 12 January 2020 to 12 December 2022. The study includes all patients who underwent surgery and were subsequently diagnosed with wound dehiscence and SSIs. Specimens were collected from patients and submitted to the Microbiology Laboratory at the hospital above. Bacterial identification and susceptibility testing to antimicrobials were performed using the Vitek 2 Compact System (bioMerieux, Marcy l'Etoile, France). Patient information was sourced from medical records. Out of 172 samples, 151 (87.8%) yielded positive cultures. Among these, 151 (87.8%) were found to be positive. Gram-negative bacteria were found to be most prevalent, with Escherichia coli (20.2%) and Pseudomonas aeruginosa (19.6%) being the most frequently isolated bacteria. The bacteria isolated were mostly susceptible to amikacin (72.1%), followed closely by meropenem (71.4%). This information could contribute to the development of an empirical antibiotic therapy protocol for wound dehiscence or SSI cases in this local context.
Keywords: Antibiotics; bacterial infection; postoperative complication; surgical site infection